HUBUNGAN KECEMASAN MATEMATIKA DAN KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA: SYSTEMATIC LITERATURE REVIEW - Aisha Budiman; Heni Pujiastuti; Maman Fathurrohman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research intends to examine the association between mathematics anxiety and students’ self-regulated learning within mathematics instruction by applying the Systematic Literature Review (SLR) approach. The investigation employed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework consisting of identification, screening, eligibility, and included stages. The process of collecting articles was conducted through Google Scholar and GARUDA databases by employing the keywords “mathematics anxiety”, “self-regulated learning”, and “mathematics learning”. The selected publications were issued during 2016–2025. According to the filtering procedure, 9 studies satisfied the inclusion requirements. The findings revealed that mathematics anxiety adversely influences students’ mathematics learning, including academic achievement, mathematical communication competence, critical thinking ability, and mathematical literacy. Conversely, self-regulated learning contributes positively to students’ mathematical proficiency. Furthermore, the synthesis findings demonstrate an association between mathematics anxiety and self-regulated learning, in which effective self-regulated learning assists students in managing emotions and dealing with pressure during mathematics learning. Consequently, educators are required to apply instructional strategies capable of minimizing mathematics anxiety while strengthening students’ self-regulated learning so that mathematics learning may proceed effectively.